2012
DOI: 10.3109/01902148.2012.715364
|View full text |Cite
|
Sign up to set email alerts
|

Mechanostructural adaptations preceding postpneumonectomy lung growth

Abstract: In many species, pneumonectomy results in compensatory growth in the remaining lung. Although the late mechanical consequences of murine pneumonectomy are known, little is known about the anatomic adaptations and respiratory mechanics during compensatory lung growth. To investigate the structural and mechanical changes during compensatory growth, mice were studied for 21 days after left pneumonectomy using microCT and respiratory system impedance (FlexiVent). Anatomic changes after left pneumonectomy included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 41 publications
(47 reference statements)
1
25
0
Order By: Relevance
“…In contrast to the three lobes in the human right lung, rodents have an additional posterior mediastinal lobe, variously referred to as the cardiac, retrocaval, or median lobe. Prior studies have demonstrated that the cardiac lobe is displaced in the left hemithorax after PNX (8,10). Intriguingly, the cardiac lobe demonstrates the greatest relative increase in compensatory lung growth (17).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast to the three lobes in the human right lung, rodents have an additional posterior mediastinal lobe, variously referred to as the cardiac, retrocaval, or median lobe. Prior studies have demonstrated that the cardiac lobe is displaced in the left hemithorax after PNX (8,10). Intriguingly, the cardiac lobe demonstrates the greatest relative increase in compensatory lung growth (17).…”
Section: Discussionmentioning
confidence: 98%
“…Preliminary experiments in our laboratory demonstrated that the chest wall contributed less than 15% to absolute impedance measurements and did not influence the time course or reproducibility of the observed mechanical changes in the lung (8,10). The constant-phase model (11) was fit to the input impedance to derive Newtonian resistance (R n), tissue damping (G), tissue elastance (H), and hysteresivity () as described below:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice undergoing surgical resection had constant heart rate and oximetry monitoring [13]. In mice undergoing surgical resection, the anterior chestwall was removed and lobar exclusion performed by clamp occlusion of the lobar bronchus and corresponding arterial blood supply.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to all measurements, the pressure transducers and ventilator tubing of the FlexiVent (SciReq, Montreal, QC) were calibrated as described [13]. After intubation, mice were transferred to the FlexiVent system (SciReq) for pulmonary mechanics studies.…”
Section: Methodsmentioning
confidence: 99%